2019
DOI: 10.1016/j.abrep.2019.100175
|View full text |Cite
|
Sign up to set email alerts
|

Pilot randomized controlled trial of an online intervention for problem gamblers

Abstract: Introduction This pilot randomized controlled trial sought to evaluate whether an online intervention for problem gambling could lead to improved gambling outcomes compared to a no intervention control. Participants were recruited through a crowdsourcing platform. Methods Participants were recruited to complete an online survey about their gambling through the Mechanical Turk platform. Those who scored 5 or more on the Problem Gambling Severity Index and were thinking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Notably, our observations were still substantially below other recent crowdsourced studies, despite the use of broadly similar advertisements. For example, Kim and Hodgins (2017) (Cunningham et al, 2017(Cunningham et al, , 2019. Additionally, clinical research relies mostly on treatment seeking populations which represent only a small proportion of individuals with an addictive disorder (Compton et al, 2007;Slutske, 2006 Mishra and Carleton (2017) reported 7.3% and 9.9% failed attention checks in two separate studies; however, the results of their analysis were consistent regardless of the inclusion/exclusion of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our observations were still substantially below other recent crowdsourced studies, despite the use of broadly similar advertisements. For example, Kim and Hodgins (2017) (Cunningham et al, 2017(Cunningham et al, , 2019. Additionally, clinical research relies mostly on treatment seeking populations which represent only a small proportion of individuals with an addictive disorder (Compton et al, 2007;Slutske, 2006 Mishra and Carleton (2017) reported 7.3% and 9.9% failed attention checks in two separate studies; however, the results of their analysis were consistent regardless of the inclusion/exclusion of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence of their efficacy in other fields, there is a paucity of research investigating the effectiveness of internet-based therapeutic interventions for the treatment of problem gambling. A limited number of recent randomised trials have, however, found that PSD iCBT for problem gambling is effective in improving gambling and psychological outcomes up to 12 months following treatment [ 29 , 30 , 31 , 32 , 33 , 34 ], although some have found no differences compared to a no intervention control group [ 31 ] or brief online personalised feedback [ 34 ]. Moreover, adding a separate mental health [ 33 ] or alcohol use intervention [ 32 ] to iCBT has not improved outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The second sample used in this study was recruited through TurkPrime [25], a panel service that allows researchers to target specific demographic groups. Prime Panels provides researchers with access to members of a number of market research panels through a Web interface similar to Amazon’s crowdsourcing platform Mechanical Turk, which has been found to be an effective method to recruit study participants online across a wide spectrum of disciplines [27-34]. However, TurkPrime offers a proportional matching sampling approach.…”
Section: Methodsmentioning
confidence: 99%